2013
DOI: 10.1186/1477-7819-11-291
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the BRAFV600E mutation in papillary thyroid microcarcinoma and clinicopathologic factors

Abstract: BackgroundThe BRAFV600E mutation, which accounts for about 60–80% papillary thyroid carcinoma(PTC), has been identifiedas a prognostic marker for risk stratification of PTC patients. However, the BRAFV600E mutation as a prognostic marker in papillary thyroid microcarcinoma (PTMC) is unclear.MethodsWe performed a retrospective review of 101 patients who underwent surgery for PTMC. We studied the prevalence of the BRAFV600E mutation. The associations between the BRAFV600E mutation and clinicopathologic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 12 publications
4
45
5
Order By: Relevance
“…To date, many studies suggested that Hashimoto's thyroiditis was associated with higher frequency of wild-type BRAF. 12,[23][24][25] In this study, DLI with positive TPOAb was a negative independent factor of BRAF V600E mutation and extrathyroidal extension in PTC but DLI without TPOAb was not. [5][6][7][8] However, there were also many studies that reported the BRAF status was not associated with Hashimoto's thyroiditis, or BRAF V600E mutation was even more frequently observed when Hashimoto's thyroiditis was present.…”
Section: Discussionmentioning
confidence: 46%
“…To date, many studies suggested that Hashimoto's thyroiditis was associated with higher frequency of wild-type BRAF. 12,[23][24][25] In this study, DLI with positive TPOAb was a negative independent factor of BRAF V600E mutation and extrathyroidal extension in PTC but DLI without TPOAb was not. [5][6][7][8] However, there were also many studies that reported the BRAF status was not associated with Hashimoto's thyroiditis, or BRAF V600E mutation was even more frequently observed when Hashimoto's thyroiditis was present.…”
Section: Discussionmentioning
confidence: 46%
“…In contrast, BRAFV600E may have relatively limited prognostic utility in areas, such as Korea, where the BRAFV600E mutation has an extremely high prevalence (Jung et al . 2010, Choi et al . 2013, Chung et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence is the most commonly described clinical and pathological feature associated with this mutation [Xing, 2010;Sancisi et al, 2012;Melo et al, 2015;Tavares et al, 2016]. In the majority of the series displaying associations between the BRAF V600E mutation and diseasespecific mortality, the association, when present, is dependent on underlying clinical and pathological features [Fugazzola et al, 2006;Xing, 2007;Ito et al, 2009;Kwak et al, 2009;Lee et al, 2009;Handkiewicz-Junak et al, 2010;Kim TH et al, 2012;Kurtulmus et al, 2012;RicarteFilho et al, 2012;Sarne, 2012;Tufano et al, 2012;Choi et al, 2013;Xing et al, 2013Xing et al, , 2014Xing et al, , 2015George et al, 2015;Melo et al, 2015;Shi et al, 2015]. Henke et al [2015] corroborated these findings in a study involving 508 patients with PCT where the BRAF mutation was present in 67% of the cases.…”
Section: Braf Mutations In Tcdfcmentioning
confidence: 99%